Safety and feasibility of revisional bariatric surgery following Laparoscopic Adjustable Gastric Band – Outcomes from a large UK private practice. Issue 4 (July 2021) - Super, Jonathan; Charalampakis, Vasileios; Tahrani, Abd A.; Kumar, Sajith; Bankenahally, Rajneesh; Raghuraman, Govindan; Jambulingam, P.S.; Kelly, Jamie; Ammori, Basil J.; Singhal, Rishi
Highlights: Safety and feasibility of private revisional bariatric surgery is unexplored. One-stage conversions are feasible and do not detrimentally affect morbidity. Success following revisional surgery is independent of indication for revision. Weight loss outcomes are independent of weight loss following primary surgery. Abstract: Background: Revisional bariatric surgery is unavoidable in a proportion of patients. Despite its need, the development of this speciality has been hampered by its complexity and preferred delivery in institutional set ups. Although primary bariatric surgery can be delivered in the private sector; safety and feasibility of revisional bariatric surgery remains unexplored in this setting. Materials and methods: Patients undergoing revisional bariatric surgery following previous Laparoscopic Adjustable Gastric Band (LAGB) between 2008 and 2019 at a single private bariatric unit with a minimum follow up of at least 6 months were included. The primary aim was safety outcomes and 30-day morbidity. Results: 178 patients with BMI of 45.6 ± 8.2 kg/m 2 underwent revisional bariatric surgery. One stage conversion was performed for 86.5% of the cases. At 9.5 ± 5.3 months follow up, BMI and percentage excess BMI loss were 31.8 ± 6.2 kg/m 2 and 62.6 ± 40% respectively. There was no mortality, and the major complication rate was 2.8%. There was no statistically significant difference in the incidence of complications based on one-stage vs. two-stage conversion (p = 0.52). There were no differences in weight loss outcomes post-revisional surgery according to the indication for revision ( p = 0.446) or weight loss following primary surgery ( p = 0.12). Conclusion: Revisional bariatric surgery can be delivered safely in the private sector with good outcomes. One-stage conversions are feasible and do not detrimentally affect the morbidity of the procedure or the weight loss outcomes. More importantly, success following revisional surgery is independent of the indication for revision and weight loss outcomes following primary surgery.